Delegation of GP-home visits to qualified practice assistants: assessment of economic effects in an ambulatory healthcare centre - Fleßa Steffen; Heymann Romy; Matzke Melanie; Meinke Claudia; van den Berg Neeltje; Hoffmann Wolfgang (BMC, 2010)
Abstract Background Against the background of a decreasing number of general practitioners (GPs) in rural regions in Germany, the AGnES-concept (AGnES = GP-supporting, community-based, e-health-assisted, systemic intervention) supports the delegation of regular GP-home visits to qualified practice assistants. The concept was implemented and evaluated in different model projects in Germany. To explore the economic effects of this concept, the development of the number of home visits in an ambulatory healthcare centre was analysed and compared with the number of home visits in the surrounding county. Methods Information about GP-home visits was derived from reimbursement data of the ambulatory healthcare centre and a statutory health insurance. Information about home visits conducted by AGnES-practice assistants was collected from the project documentation over a time period of 12 consecutive quarter years, four quarter years before the beginning of the project and 8 quarter years while the project was implemented, considering background temporal trends on the population level in the study region. Results Within the ambulatory healthcare centre, the home visits by the GPs significantly decreased, especially the number of medically urgent home visits. However, the overall rate of home visits (conducted by the GPs and the AGnES-practice assistants together) did not change significantly after implementation of the AGnES-concept. In the surrounding county, the home visit rates of the GPs were continuous; the temporal patterns were approximately equal for both usual and urgent home visits. Conclusion The results of the analyses show that the support by AGnES-practice assistants led to a decrease of GP-home visits rather than an induction of additional home visits by the AGnES-practice assistants. The most extended effect is related to the medically urgent home visits rather than to the usual home visits.